Modelling the influence of coral-reef-derived dimethylsulfide on the atmosphere of the Great Barrier Reef, Australia - Jackson, Rebecca L.; Woodhouse, Matthew T.; Gabric, Albert J.; Cropp, Roger A.; Swan, Hilton B.; Deschaseaux, Elisabeth S. M.; Trounce, Haydn (Frontiers in Marine Science, 2022)
Marine dimethylsulfide (DMS) is an important source of natural sulfur to the atmosphere, with potential implications for the Earth’s radiative balance. Coral reefs are important regional sources of DMS, yet their contribution is not accounted for in global DMS climatologies or in model simulations. This study accounts for coral-reef-derived DMS and investigates its influence on the atmosphere of the Great Barrier Reef (GBR), Australia, using the Australian Community Climate and Earth System Simulator Atmospheric Model version 2 (ACCESS-AM2). A climatology of seawater surface DMS (DMSw) concentration in the GBR and an estimate of direct coral-to-air DMS flux during coral exposure to air at low tide are incorporated into the model, increasing DMS emissions from the GBR region by 0.02 Tg yr-1. Inclusion of coral-reef-derived DMS increased annual mean atmospheric DMS concentration over north-eastern Australia by 29%, contributing to an increase in gas-phase sulfate aerosol precursors of up to 18% over the GBR. The findings suggest that the GBR is an important regional source of atmospheric sulfur, with the potential to influence local-scale aerosol-cloud processes. However, no influence on sulfate aerosol mass or number concentration was detected, even with a reduction in anthropogenic sulfur dioxide emissions, indicating that DMS may not significantly influence the regional atmosphere at monthly, annual or large spatial scales. Further research is needed to improve the representation of coral-reef-derived DMS in climate models and determine its influence on local, sub-daily aerosol-cloud processes, for which observational studies suggest that DMS may play a more important role.